Preparation and Microwave Absorbing Property of Dendritic FexCo1-x Alloys - Tian, Liangliang; Wang, Fei; Liu, Bitao; Cai, Yanhua (Asian Journal of Chemistry, 2014)
Dendritic FexCo1-x (x = 0.1, 0.2, 0.3, 0.4, 0.5) alloys were synthesized by low temperature hydrothermal method. Morphology, composition, structure, magnetic property and microwave absorbing property of the FexCo1-x alloys were characterized by scanning electron microscopy, energy disperse spectroscopy, X-ray diffraction, vibrating sample magnetometer and vector network analyzer, respectively. It was found that the composition of the FexCo1-x alloys conforms to the stoichiometric ratio. X-ray diffraction patterns reveal that the alloys show mixed structure when Fe content is lower than 0.3. However, when Fe content is higher than 0.3, the alloys show only bcc structure. The saturation magnetization (Ms) increases and coercivity (Hc) decreases with the increase of the Fe content. The microwave absorbing measurements reveal that the minimum reflection loss of Fe0.1Co0.9 alloy is -17.8 dB at 6.4 GHz with a thickness of 2.5 mm, showing the best microwave absorbing property among all the obtained alloys.